Effect of Implementation of Quality Assurance and Business Incubator on Entrepreneur Quality of SMEs in East Java - Arifin, Syaiful; Wahyono, Rudy; Sihwahjoeni, Sihwahjoeni (International Conferences SDGs 2030 Challenges and Solutions, 2030)
This study aims to describe quality assurance, a business incubator, and entrepreneur quality, and analyze the influence of quality assurance and business incubator on entrepreneur quality. This research is explanatory research. Explanatory research is intended to obtain clarity or explain a phenomenon, explain the relationship, test the influence of variables. The analysis technique used multiple regression analysis. Based on the analysis result shows that quality assurance is formed by management system aspect and technical requirement, the main contribution of an establishment of quality assurance is management system aspect. Business incubators are formed by new business growth, job creation, economic turnaround, a failure rate of new business development, and ability to obtain investment funds. The main contribution to the establishment of business incubators is the addition of new business. The entrepreneur quality is made up of a strategic orientation driven by opportunity perceptions, commitment to opportunities, resource commitments, control of resources and a realistic vision. The main contribution of entrepreneur quality is a commitment to opportunities. Quality assurance has a significant effect on entrepreneur quality. Business incubator has a significant effect on the quality of an entrepreneur.